Osteoporotic vertebral fractures and subsequent fractures: risk factors from a retrospective observational study of patients with osteoporosis - Fan, Mingxing; Lu, Ran; Wu, Jiayuan; Huang, Jie; Fang, Yanming (Frontiers in Molecular Biosciences, 2025)
PurposeOsteoporosis is a progressive, systemic, skeletal disorder characterized by increased bone fragility and susceptibility to fracture. Prior fractures are a strong predictor of subsequent fractures, but it is essential to identify further clinical and demographic characteristics of patients with osteoporosis that are associated with subsequent fracture risk.MethodsIn this retrospective observational cohort study, male and female patients over the age of 55 years with osteoporosis who experienced vertebral fractures between 2019 and 2021 were included. All patients’ basic clinical data, serum biochemical and bone turnover markers, bone mineral density, and other indicators were recorded uniformly. The incidence of subsequent fractures during the two-year follow-up period was analyzed. Independent risk factors for subsequent fractures were identified by binary logistic regression analysis.ResultsA total of 1,096 patients were included. Of these, 311 (28.4%) patients suffered a subsequent fracture during the two-year follow-up period. The incidences of subsequent fracture sites were 18.4% vertebral, 14.2% forearm/wrist/hand, and 9.9% hip/femur. Compared with the non-subsequent fracture group (non-SFG), binary logistic regression analysis showed that body mass index (BMI) (OR [95% CI] 0.825 [0.720–0.945]; P = 0.006), femoral neck bone mineral density (BMD) T-score (OR [95% CI] 0.067 [0.012–0.385]; P = 0.002), and C-terminal telopeptide of type 1 collagen (CTX) levels (OR [95% CI] 6.089 [1.735–21.375]; P = 0.005) were independent risk factors associated with subsequent fractures.ConclusionPatients with osteoporosis and previous vertebral fractures are at a higher risk of further fractures at a two-year follow-up period. BMI, femoral neck BMD T-score, and CTX levels were independent risk factors for refracture. Integrating BMI, femoral neck BMD, and CTX levels into an individualized care plan for patients with osteoporotic vertebral fractures may help prevent subsequent fractures in high-risk populations.